Ruthenium half-sandwich complexes containing novel anionic (phosphino) tetraphenylborate ligands - Larocque, Timothy G. (My University, 2009)
In an attempt to expand upon previous work involving ruthenium-arene complexes bearing anionic (phosphino) tetraphenylborate ligands, and possibly provide further insight into the products obtained, a series of metal complexes containing these anionic phosphines were synthesized.
Keywords: Ruthenium compounds